REVISITING HADITH INTERPRETATION THROUGH GEOGRAPHY: EXTENDING MICHAEL A. COOK’S EXTERNAL CRITERIA THEORY - Famellia, Zella; Sattar, Abdul (UIN Walisongo Semarang, 2025)
A hadith cannot always be understood solely throught its textual, it often requires a specific approach to uncover its proper contextual interpretation. The geographical approach is one such contextual method that helps reveal the true meaning of a hadith. This study adopts the theory of external criteria, as one of the essential aspects to examine in hadith research is the location where the hadith was conveyed. The purpose of this research is to explore the necessity of the geographical approach as an external criterion in understanding hadiths and to present examples of its application in several hadiths. This research employes a qualitative descriptive method with a library research design and a hadith studies approach. The finding reveals that, first, the geographical approach as an external criterion is crucial for comprehending the Prophet's hadiths. Second, examples include: 1) hadiths on the dynamic direction of the Qibla according to a Muslim’s location; 2) hadiths on toilet etiquette related to facing or turning away from the Qibla depending on the setting; 3) hadiths on garments such as white robes that adapt to local culture and climate.